Timing of Elective Delivery in Gastroschisis: A Decision and Cost Effectiveness Analysis - Harper, Lorie M. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: To determine the most cost-effective delivery timing in pregnancies complicated by gastroschisis using a decision-analytic model. METHODS: We created a decision analytic model to compare planned delivery at 35, 36, 37, 38, & 39 weeks. Outcomes considered were stillbirth, death within 1 year of life, & respiratory distress syndrome (RDS). Probability estimates of events (stillbirth, complex gastroschisis, and RDS at each gestational age, and risk of death in simple and complex gastroschisis), utilities, & costs assigned to the outcomes were obtained from published literature. Cost analysis was from a societal perspective using a willingness to pay threshold of $100,000 per surviving infant. Outcomes and costs were considered through 1 year of life. Multi-way sensitivity analyses were performed to address uncertainties in baseline assumptions. RESULTS: In the base case analysis, delivery at 38 weeks is the most cost-effective strategy. Planned delivery at 35 weeks was associated with the fewest stillbirths and deaths within 1 year, due largely to a difference in ongoing risk of stillbirth. In Monte Carlo simulation when every variable was varied over its entire range, delivery at 38 weeks is cost-effective compared to 39 weeks in 76% of trials and delivery at 37 weeks is cost-effective in 69% of trials. Delivery at 38 weeks resulted in 3 additional cases of RDS for every 100 stillbirths or deaths within 1 year prevented. CONCLUSIONS: In pregnancies complicated by gastroschisis, the most cost-effective timing of delivery is 38 weeks. Few additional cases of RDS are caused for every 1 stillbirth or death within 1 year prevented with delivery at 37–38 weeks.